Prevalensi Penularan HIV di Kota Tangerang Tahun 2023 - Farid Amin, Ahmad; Purnamasari, Dewi (Ikatan Ahli Kesehatan Masyarakat Indonesia Kota Tangerang Selatan, 2024)
Human Immunodeficiency Virus (HIV) attacks the human immune system. Risky sexual behavior and injecting drug use are the main factors of HIV transmission. This study aims to describe the prevalence of HIV in Tangerang City, using data from SIHA 2.1 for September to December 2022. The data was analyzed descriptively. Results show that 19,411 people were tested for HIV, with 271 new cases confirmed. The majority were male (84.3%), aged 20–29 years (41.57%), and the largest affected group was Men who have Sex with Men (MSM) (46.49%). Additionally, 32.1% of People Living with HIV/AIDS (PLHIV) had not started ART. The HIV transmission continues to rise, particularly in the productive age group, which could increase the health care burden in Tangerang. Immediate action is required to address this issue. A massive public awareness campaign is essential to prevent further HIV spread. Expanding and increasing HIV testing is crucial, along with optimizing and expanding Care, Support, and Treatment (CST) services to improve accessibility for PLHIV. Without these measures, the number of HIV cases will likely continue to grow.